Iowa RBA, April 1, 1996 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for April 1, 1996. Highlights of the update include sightings of a Hermit Thrush, Glaucous Gull, Fish Crow, Smith's Longspur and Sandhill Cranes. Also included are handwritten notes for the next week's update with sightings of a Great Egret and a Bonaparte's Gull. Epson - sheet feed/flatbed